Mutations in the cytoplasmic domain of the influenza virus hemagglutinin affect different stages of intracellular transport (The Rockefeller University Press, 1985)
Mutations have been introduced into the cloned DNA sequences coding for influenza virus hemagglutinin (HA), and the resulting mutant genes have been expressed in simian cells by the use of SV40-HA recombinant viral vectors. In this study we analyzed the effect of specific alterations in the cytoplasmic domain of the HA molecule on its rate of biosynthesis and transport, cellular localization, and biological activity. Several of the mutants displayed abnormalities in the pathway of transport from the endoplasmic reticulum to the cell surface. One mutant HA remained within the endoplasmic reticulum; others were delayed in reaching the Golgi apparatus after core glycosylation had been completed in the endoplasmic reticulum, but then progressed at a normal rate from the Golgi apparatus to the cell surface; another was delayed in transport from the Golgi apparatus to the plasma membrane. However, two mutants were indistinguishable from wild-type HA in their rate of movement from the endoplasmic reticulum through the Golgi apparatus to the cell surface. We conclude that changes in the cytoplasmic domain can powerfully influence the rate of intracellular transport and the efficiency with which HA reaches the cell surface. Nevertheless, absolute conservation of this region of the molecule is not required for maturation and efficient expression of a biologically active HA on the surface of infected cells.